Wind Turbine Technology 2014
DOI: 10.1201/b16587-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecomoulding of Composite Wind Turbine Blades Using Green Manufacturing RTM Process

Abstract: Abstract:The gearbox is one of the most expensive components of the wind turbine system. In order to refine the design and hence increase the long-term reliability, there has been increasing interest in utilizing time domain simulations in the prediction of gearbox design loads. In this study, three problems in time domain based gear contact fatigue analysis under dynamic conditions are discussed: (1) the torque reversal problem under low wind speed conditions, (2) statistical uncertainty effects due to time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Thus the long-term contact fatigue results should be conservative. In addition, a simpler method of performing the time domain-based long-term contact fatigue analysis of gears was suggested by Dong et al; more details can be found in [48]. In this study only the torques in the main shaft are considered.…”
Section: Post-processing Of Simpack Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the long-term contact fatigue results should be conservative. In addition, a simpler method of performing the time domain-based long-term contact fatigue analysis of gears was suggested by Dong et al; more details can be found in [48]. In this study only the torques in the main shaft are considered.…”
Section: Post-processing Of Simpack Resultsmentioning
confidence: 99%
“…Each wind speed is simulated for 700 s, and the first 100 s is discarded. Additional details can be found in [48]. Fig.…”
Section: Global Response Analysis Of a Land-based Nrel 750 Kw Wind Tumentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the drivetrain design loads and understand the load effects in operational, parked or fault conditions of onshore wind turbines, various studies on dynamic response analysis [53,[117][118][119][120][121][122] have been carried out using finite element or multibody simulation codes. For example, Dong et al [119] performed dynamic response analysis of a 750-kW wind turbine drivetrain and analyzed the dynamic gear contact forces. Jiang et al [53] also performed multibody simulation of the same drivetrain and focused on the dynamic loads on the planetary bearings.…”
Section: Mechanical and Electrical Componentsmentioning
confidence: 99%
“…Structural reliability analysis is typically based on a model that describes the response of a system, such as stress, maximum deformation and contact force time series, as a function of random variables. 16,17 In this study, the contact force of a gear and the bending torque of a shaft were used as random variables to analyse the reliability of a drive system. In 1950, Tuplin 18 laid the theoretical basis for gear system dynamics research.…”
Section: Introductionmentioning
confidence: 99%